ANALYZING THE EFFECT OF MARKETING MIX, SERVICE QUALITY AND BRAND EQUITY ON CONSUMER BUYING DECISION IN INDOMARET MANADO - Mongdong, Vilanri G; Tumewu, Ferdinand J (Universitas Sam Ratulangi, 2015)
Nowadays retail industry has been growing quite fast supported by the consumer behavior that has begun to shift from traditional to modern retail market. APRINDO predicted that the growth would be around 10% by 2015. Indomaret franchise is the pioneer in Indonesia. The objective of this research is to identify the effect of marketing mix, service quality and brand equity on consumer buying decision. In this research, the population refers to the consumer of Indomaret Manado with cluster sampling technique and sample size as many as 100 respondents. This research used quantitative analysis by using questionnaires and used multiple regression analysis. Result showed that marketing mix, service quality and brand equity have significant effect on consumer buying decision simultaneously. Brand equity has significant partial effect on consumer buying decision while marketing mix and service quality do not have partial significant effect on consumer buying decision.Â Indomaret Manado should add product varieties especially for fresh product to improve marketing mix and increase employeeâ€™s ability to serve customers well to improve the service quality. Keywords: marketing mix, service quality, brand equity, consumer buying decision